Impact of aircraft rubber tyre fragments on aluminium alloy plates: II—Numerical simulation using LS-DYNA - Karagiozova, D.; Mines, R.A.W. (International journal of impact engineering, 2007)
A discrete model for a reinforced rubber-like material is proposed in order to simulate numerically a debris tyre impact on a typical structure of an aircraft when using the FE code LS-DYNA. The model is calibrated using the static and dynamic test data for the actual tyre material. The dynamics of the tyre projectile is validated when comparing the numerical predictions with the response of a square aluminium alloy plate subject to a ribbon projectile impact having different initial velocities and impacting the plate at an angle of 30°. Good agreement is obtained in terms of the strains in the plate caused by the ribbon impact. The numerically predicted deformations of the projectile also represent well the dynamics of the tyre ribbon recorded during the experiments. Some characteristic features of a soft projectile impact on a deformable plate are discussed. The developed model is then extended to the simulation of a full-scale impact test, and good agreement is shown between experiment and simulation.